Athlete's Heart Assessed by Sit-Up Strength Exercises in Military Men and Women: The CHIEF Heart Study - Lin, Yu-Kai; Tsai, Kun-Zhe; Han, Chih-Lu; Lee, Jiunn-Tay; Lin, Gen-Min (Frontiers in Cardiovascular Medicine, 2022)
Background Greater changes in cardiac structure and function in response to physical training have been observed more often in male athletes than in female athletes compared with their sedentary controls. However, studies for the sex-specific cardiac remodeling related to strength exercises in Asian athletes are rare. Methods This study included 580 men and 79 women, with an average age of 25 years, for a 6-month military training program in Taiwan. Both men and women attended a 2-min sit-up test to assess muscular strength after the training. The test performance falling one standard deviation above the mean (16%) was to define the superior eliteness of athletes. Cardiac structure and function were investigated by electrocardiography and echocardiography for men and women. Multiple logistic regression was used to determine the predictors of elite athlete status. Results In men, greater QTc interval, left ventricular mass adjusted to body surface area (LVMI), lateral mitral E'/A' ratio and right ventricular systolic pressure, and lower diastolic blood pressure were independent predictors of elite strength athletes in the sit-up test [odds ratio (OR) and 95% confidence intervals: 1.01 (1.00, 1.02), 1.02 (1.00, 1.04), 1.45 (1.06, 1.98), 1.13 (1.06, 1.23), and 0.96 (0.93, 0.99), respectively. In contrast, in women, the greater right ventricular outflow tract dimension was the only independent predictor of elite strength athletes in the sit-up test [OR: 1.26 (1.04, 1.53)]. Conclusions In the 2-min sit-up test, cardiac characteristics differ between elite male and female athletes. While greater QTc interval, LVMI, and diastolic function of left ventricle predict the eliteness of male strength athletes, greater right ventricular chamber size characterizes elite female strength athletes.